The diagnostic utility of serum IgG4 concentrations in IgG4-related disease - Carruthers, Mollie N; Khosroshahi, Arezou; Augustin, Tamara; Deshpande, Vikram; Stone, John H (Annals of the rheumatic diseases, 2015)
Objectives We evaluated the sensitivity, specificity and positive and negative predictive values of elevated serum IgG4 concentrations for the diagnosis of IgG4-RD. Methods Between 2001 and 2011, 190 unique patients had elevated serum IgG4 measurements. We reviewed electronic medical records to determine the indication for IgG4 measurement and underlying clinical diagnosis. Additionally, we reviewed the records of 190 other randomly selected patients from a pool of 3360 with normal results, to evaluate test characteristics of the IgG4 measurement. Results Among 380 patients analysed, 72 had either probable or definite IgG4-RD. Sixty-five of the 72 IgG4-RD patients had elevated serum IgG4 concentrations (mean: 405 mg/dL; range 140–2000 mg/dL), for a sensitivity of 90%. Among the 308 subjects without IgG4-RD, 125 had elevated IgG4 (mean: 234 mg/dL; range 135–1180 mg/dL) and 183 had normal IgG4 concentrations, for a specificity of 60%. The negative predictive value of a serum IgG4 assay was 96%, but the positive predictive value only 34%. Analysis of the serum IgG4/total IgG ratio did not improve these test characteristics. Doubling the cutoff for IgG4 improved specificity (91%) but decreased sensitivity to 35%. Discussion Multiple non-IgG4-RD conditions are associated with elevated serum IgG4, leading to poor specificity and low positive predictive value for this test. A substantial subset of patients with biopsy-proven IgG4-RD do not have elevated serum IgG4. Neither doubling the cutoff for serum IgG4 nor examining the serum IgG4/IgG ratio improves the overall test characteristics for the diagnosis of IgG4-RD.